the Efficacy of Clove Oil Cream in Treating Tinea Pedis: Overcoming Antifungal Resistance - Salsabil A. Altumi; Marzoga R. Salem; Tamara A. Alnaied; Saja Fraj Shandola; Shahd A. Aljlidi (Surman Journal of Science and Technology, 2026)
Tinea pedis remains a significant global health challenge, further complicated by the emergence of antifungal resistance to conventional treatments. This study evaluated the in vitro antifungal efficacy of clove oil (Syzygium aromaticum) against clinical dermatophyte isolates and developed a stable topical formulation for therapeutic use. Fungal samples were isolated from symptomatic patients, and their susceptibility was tested using the disc diffusion method in comparison with Miconazole 2%. Subsequently, an oil-in-water (O/W) topical cream was formulated. The results demonstrated that clove oil possesses potent antifungal activity across all isolates, significantly outperforming Miconazole (P < 0.05). Notably, clove oil exhibited strong inhibitory effects against a Miconazole-resistant strain, producing a 3.2 mm inhibition zone where the standard treatment failed. Preliminary clinical application in a pilot case series (n=2) showed marked reduction in erythema and scaling after 10 days of twice-daily application. These findings suggest that clove oil is a promising natural alternative for managing resistant fungal infections, providing a foundation for larger-scale clinical evaluation.